Network Patterns of Village Head Political Dynasty in Maggenrang Village - Ikhsan, Andi Ahmar Ihwal; Hawing, Hardianto; Hamrun, Hamrun; Alim, Irwan (Journal of Contemporary Local Politics, 2024)
The political dynasty network pattern is a series of political strategies aimed at obtaining power by passing on positions to individuals who have family ties to previous power holders. Based on this, this study aims to determine the pattern of dynastic political network formation and its impact on community political behavior in Maggenrang Village, Kahu Subdistrict, Bone Regency. This research uses a qualitative method to describe and explain the patterns of the formation of political dynasty networks and their impact on political behavior. Data collection techniques include observation, interviews, and documentation. The results showed that the dynastic political network pattern in Maggenrang Village includes several aspects. First, stable economic capital and family relations with the previous village head make the current village head part of dynastic politics. Second, cultural capital, which includes the character and competence of the village head, is very important because it has an impact on the decision-making process and actions. Third, good social capital can be seen in the active role of the village head in community activities. Finally, symbolic capital is less strong but still able to prosper its people. The impact of political dynasties in Maggenrang Village is the limitation of opportunities for other individuals who are more worthy to hold the position of village head.